The Role of Sense of Belonging and Professional Skepticism in University’s Internal Auditor Function - Aprina Nugrahesthy Sulistya Hapsari; Nabilla Ningrum (Politeknik Negeri Madiun, 2022)
This study aims to describe the role of Sense of Belonging (SoB) and professional skepticism in supporting the performance of internal auditors at Satya Wacana Christian University (SWCU). This study uses both primary data by conducting in-depth interview with financial, academic and non-academic internal auditors, auditee and internal control body at SWCU and the secondary data were obtained from documents such as code of ethics, audit instruments and internal auditors charter. This study is a qualitative descriptive research and uses two types of triangulation which is data triangulation and source triangulation. The results of this study shows that the role of SoB and professional skepticism has been implemented in SWCU and both roles encourage the internal auditor’s function in university.